Economic Growth Paths in the CEE Countries and in Selected Emerging Economies, 1993-2007 - Ryszard Rapacki; Mariusz Próchniak (Research in Economics and Business: Central and Eastern Europe, 2010)
This paper presents an empirical analysis of the economic growth paths in two groups of countries. The first group consists of ten Central and Eastern European (CEE) countries. The second group constitutes a benchmark and encompasses 29 emerging economies in other regions of the world. Our analysis covers the period 1993-2007. We aim to compare the growth paths of the CEE countries and the reference emerging economies. We use two econometric methods: income-level convergence analysis and growth accounting exercise. Th e main fi ndings are as follows. (1) Th e individual CEE countries and the CEE-10 group, as a whole, displayed a relatively rapid economic growth, compared with the remaining 29 emerging economies. (2) Our analysis does not confirm that fast economic growth of the CEE-10 countries (in comparison with the other emerging economies) resulted from the mechanism of absolute convergence. There were signs, however, that the former group was subject to a conditional beta convergence. (3) Rapid economic growth of the CEE-10 countries has been driven to a large extent by the increase of total factor productivity (TFP).
Keywords: O47; P24; 330; economic growth; convergence; economic growth; convergence